Beam longitudinal dynamics simulation studies - H. Timko; S. Albright; T. Argyropoulos; H. Damerau; K. Iliakis; L. Intelisano; B. E. Karlsen-Baeck; I. Karpov; A. Lasheen; L. Medina; D. Quartullo; J. Repond; et al. (Physical Review Accelerators and Beams, 2023)
The beam longitudinal dynamics code blond, utilized tool, has been developed at CERN since 2014. It has emerged as a central tool for conducting longitudinal beam dynamics simulations. In this paper, we present this modular simulation suite and the various physics models that can be included and combined by the user. We detail the reference frame, the equations of motion, the plethora of options for radio-frequency parameters such as phase noise, fixed-field acceleration, and feedback models for the CERN accelerators, as well as the modeling of collective effects and synchrotron radiation. We also present various methods of generating multibunch distributions matched to a given impedance model. blond is furthermore a well tested and optimized simulation suite, which is demonstrated through examples, too.